Modification of Nyamplung Seed Peeling Machine Transmission - Muhammad Ilham Alhabsyie; Wilarso; Awang Surya; Asep Saepudin; Aswin Domodite (Universitas Medan Area, 2025)
Design of a nyamplung seed peeling machine with a 0.5 HP electric motor drive source with 1400 rpm rotation using a Ø76 mm pulley transmission system with a 1:1 ratio with a v-belt type A-24. After testing, it was found that from 100% of the nyamplung seeds there were seeds that were crushed and their contents were not processed, as many as 55% of the nyamplung seeds were found, apart from that when the machine was run there were seeds that were thrown out of the hopper so that the results of the machine design were deemed not to be as expected. To overcome this problem, it is necessary to modify the previous research machine so that the peeling process between the seeds and the nyamplung shell can improve the quality. The results of the modification of the nyamplung seed peeler tool were obtained with a duration of 13 seconds, the number of nyamplung seeds was 25 pcs, of which 17 were peeled. There were 5 pcs of whatever were not peeled, and 3 pcs were crushed. The second trial had a duration of 14 seconds, the number of seeds sampled was 25, 18 were peeled, the remaining 4 were not peeled and 3 were crushed. The third trial lasted 15 seconds out of a total of 25 pieces peeled, the result was 19 pieces peeled and the remaining 2 pieces failed, 4 pieces were destroyed